2021
DOI: 10.22437/jssh.v5i2.15801
|View full text |Cite
|
Sign up to set email alerts
|

Classifying regencies and cities on human development index dimensions: Application of K-Means cluster analysis

Abstract: The Human Development Index (HDI) is a measurement that analyzes a region's development in improving human development. The government's development plan aims to create a successful and peaceful life. The unbalanced development in every regency and city in Indonesia is a typical issue during the development process. It may also be shown that the HDI level changes across regencies and cities in Indonesia. This research aims to identify Indonesian regencies and cities based on HDI indices. K-Means clustering alg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
0
2
0
2
Order By: Relevance
“…Much research has been carried out regarding the grouping of human development in Indonesia based on HDI indicators by using cluster analysis, such as hierarchical clustering [5], K-Means [4], [5], [10], K-Medoids [5], and Fuzzy C-Means [10]. The researchers found that the number of clusters is four clusters using K-Means [4], [5], [10] and Fuzzy C-Means [10], but two clusters for hierarchical clustering and five clusters for indah.fahmiyah@ftmm.unair.ac.id K-Medoids [5]. HDI grouping in a particular area in Indonesia was also carried out [1], [11], [12].…”
Section: Corresponding Authormentioning
confidence: 99%
“…Much research has been carried out regarding the grouping of human development in Indonesia based on HDI indicators by using cluster analysis, such as hierarchical clustering [5], K-Means [4], [5], [10], K-Medoids [5], and Fuzzy C-Means [10]. The researchers found that the number of clusters is four clusters using K-Means [4], [5], [10] and Fuzzy C-Means [10], but two clusters for hierarchical clustering and five clusters for indah.fahmiyah@ftmm.unair.ac.id K-Medoids [5]. HDI grouping in a particular area in Indonesia was also carried out [1], [11], [12].…”
Section: Corresponding Authormentioning
confidence: 99%
“…Karakteristik objek yang digunakan dalam analisis cluster berasal dari variabel. Variabel dalam analisis cluster harus saling bebas dan tidak memiliki korelasi satu dengan yang lain (Nurhasanah et al, 2021). Salah satu metode dalam analisis cluster adalah Model-Based Clustering yang diperkenalkan pertama kali oleh Banfield & Raftery (1993).…”
Section: Metode Analisis 1 Model-based Clusteringunclassified
“…Human Development Index (HDI) is an indicator to observe the level of human development in a region (Nurhasanah et al, 2021). Banda Aceh is one of the cities in Indonesia that is trying to improve the performance of its educational institutions to create quality human development.…”
Section: Introductionmentioning
confidence: 99%